The Dermatoglyphics, Health and Diseases in Last Ten Years' Review - Samar Abdulwahab Abdulla; Huda Abdul hameed Abdulrahman; Neyaf Majid Alageedi; Mohammed J.I. Al-Shammari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
In the art and science of dermatology, ridge patterns and surface markings are studied on the finger’s skin, palm, foot toes, and soles. It is helpful for research into illnesses that may have a hereditary component. Dermatoglyphics has developed into a practical instrument in the fields of biology, anthropology, genetics, medicine, and dentistry over the past few centuries. The state of medical dermatoglyphics today is such that different systemic illnesses are linked to fingerprint patterns. Breast cancer, smokeing tobacco, bronchial asthma, diabetes mellitus, and several others were maintained. The sophisticated and contemporary uses of dermatoglyphics in the diagnosis of various oral, systemic, and dental conditions are covered in this article. It also emphasizes how beneficial dermatoglyphics is as a medical diagnostic tool for a variety of systemic illnesses. An approach to investigating the genetic relationships of oral, craniofacial, and systemic illnesses that is easily accessible, affordable, practical, trustworthy, and noninvasive is dermatoglyphics. Therefore, dermatoglyphics is a great tool for screening the population for numerous medical and dental conditions in addition to providing personal identification.